Effect of Acupuncture Stimulation of Hegu (LI4) and Taichong (LR3) on the Resting-State Networks in Alzheimer’s Disease: Beyond the Default Mode Network - Shaozhen Ji; Hao Zhang; Wen Qin; Ming Liu; Weimin Zheng; Ying Han; Haiqing Song; Kuncheng Li; Jie Lu; Zhiqun Wang (Neural Plasticity)
It was reported that acupuncture could treat Alzheimer’s disease (AD) with the potential mechanisms remaining unclear. The aim of the study is to explore the effect of the combination stimulus of Hegu (LI4) and Taichong (LR3) on the resting-state brain networks in AD, beyond the default network (DMN). Twenty-eight subjects including 14 AD patients and 14 healthy controls (HCs) matched by age, gender, and educational level were recruited in this study. After the baseline resting-state MRI scans, the manual acupuncture stimulation was performed for 3 minutes, and then, another 10 minutes of resting-state fMRI scans was acquired. In addition to the DMN, five other resting-state networks were identified by independent component analysis (ICA), including left frontal parietal network (lFPN), right frontal parietal network (rFPN), visual network (VN), sensorimotor network (SMN), and auditory network (AN). And the impaired connectivity in the lFPN, rFPN, SMN, and VN was found in AD patients compared with those in HCs. After acupuncture, significantly decreased connectivity in the right middle frontal gyrus (MFG) of rFPN (P=0.007) was identified in AD patients. However, reduced connectivity in the right inferior frontal gyrus (IFG) (P=0.047) and left superior frontal gyrus (SFG) (P=0.041) of lFPN and some regions of the SMN (the left inferior parietal lobula (P=0.004), left postcentral gyrus (PoCG) (P=0.001), right PoCG (P=0.032), and right MFG (P=0.010)) and the right MOG of VN (P=0.003) was indicated in HCs. In addition, after controlling for the effect of acupuncture on HCs, the functional connectivity of the right cerebellum crus I, left IFG, and left angular gyrus (AG) of lFPN showed to be decreased, while the left MFG of IFPN and the right lingual gyrus of VN increased in AD patients. These findings might have some reference values for the interpretation of the combination stimulus of Hegu (LI4) and Taichong (LR3) in AD patients, which could deepen our understanding of the potential mechanisms of acupuncture on AD.